DESIGN OF INQUIRY LEARNING MODEL INTEGRATED ETHNO-STEM FOR PROFILE ANALYZING THE AROMA COMPOUND FROM HERBAL TEA EXTRACT: Received: 16th November 2023; Revised: 20th December 2023, 25th December 2023; Accepted: 14th January 2024 - Sudarmin; Kasmui; Pujiastuti, Rr. Sri Endang; Priatmoko, Sigit (LIFE: International Journal of Health and Life-Sciences, 2024)
The purpose of this research is to find a Design of an Inquiry Learning Model Integrated Ethno-Stem for Profile Analyzing the Aroma Compound from Herbal Tea Extract from tropical forest plants in Indonesia to accelerate student conservation literacy. This research is a basic research to find an Ethno-STEM integrated inquiry learning model and analysis of Aroma Compound profiles of herbal tea extracts from tropical forest plants in Indonesia. The research was conducted at the Department of Chemistry in the Natural Materials course. The research subjects are UNNES chemistry education students for the 2021/2022 academic year. The research instruments were tests, questionnaires, observation sheets, and aroma compound profile test data for herbal teas from Indonesian tropical forest plants. Trapping of aroma compound compounds from herbal teas from tropical forest plants uses Arduino sensors type MQ-9, MQ135, TGS 2602, and 2620. The stage of Development of the Ethno-STEM Integrated Inquiry Learning Model usees the Analysis, Design, Development, and Implementation. The results of the research found an Ethno-STEM integrated inquiry learning model with the Sudarmin stages. The results of the analysis of aroma compound profiles from tropical forest plants are hydrogen, propane, carbon monoxide (CO), alcohol, carbon dioxide (CO2), toluene, ammonia, acetone, heptane, and acid sulfide gas.